Blind people accept their disability (Journal of the College of Basic Education, 2023)
Individuals with visual impairments face extreme difficulties in practicing their life behaviors, due to the nature of their weak relationship with society, as a result of the loss of the sensory medium that is the most important basis for dealing with visual stimuli and acquiring knowledge, which is the sense of sight, which pushes them to make great efforts and exposes them to nervous stress and psychological tension, as well as Feelings of insecurity and confusion about life situations in general (Al-Quraiti, 1996: 201).Acquiring the necessary social skills to achieve independence and a sense of self-sufficiency is not as required for the blind, due to their limited ability to move, and their inability to observe the behavior of others.